Surgical Resection with Neoadjuvant Chemotherapy for Locoregionally Recurrent Appendiceal Cancer Invading the External Iliac Vessels - Jun Takahashi; Shingo Tsujinaka; Nao Kakizawa; Noriya Takayama; Erika Machida; Kazuki Iseya; Fumi Hasegawa; Rina Kikugawa; Yasuyuki Miyakura; Koichi Suzuki; Toshiki Rikiyama (Case Reports in Surgery)
Recent advancements in multimodal therapy can provide oncologic benefits for patients with recurrent colorectal cancer. This report presents a case of locoregionally recurrent appendiceal cancer treated with neoadjuvant chemotherapy followed by surgical resection with vascular reconstruction. A 68-year-old Japanese woman was diagnosed with appendiceal cancer and underwent ileocecal resection. The pathological evaluation revealed KRAS-mutant adenocarcinoma with the final stage of T4bN1M0. She received oral fluorouracil-based adjuvant chemotherapy. One year later, she was found to have peritoneal dissemination in the pelvic cavity and vaginal metastasis. She received an oxaliplatin-based chemotherapy followed by surgical resection. One year after the second surgery, she developed a locoregional recurrence involving the right external iliac vessels and small intestine. She received an irinotecan-based regimen with bevacizumab as neoadjuvant chemotherapy, followed by surgical resection. At first, a femoro-femoral bypass was made to secure the blood supply to the right lower extremities. Subsequently, an en bloc resection including the recurrent tumor and the external iliac vessels was completed. Surgical resection for recurrent colorectal cancer is often technically challenging because of the tumor location and invasion to adjacent organs. In this case, a surgical approach with persistent chemotherapy achieved oncologic resection of locoregionally recurrent appendiceal cancer.